2012
DOI: 10.1134/s0026261712010080
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the communities of acidophilic chemolithotrophic microorganisms in natural and technogenic ecosystems

Abstract: The communities of acidophilic chem olithotrophic microorganisms (ACM) are formed in sulfide ore deposits, mine waters, pyrite coals, the wastes of ore mining and processing industry in differ ent geographical and climatic zones, as well as in the pulps of reactors for the technologies of bacterialchemical oxidation of sulfide ore concentrates, i.e., in the presence of sulfide minerals and their oxidation products, elemental sulfur, reduced sulfur com pounds, and ferrous iron. As a result of their activity, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…iron oxidizers) and Crenarchaeota ( e.g . sulfur oxidizers) are actually favored in acidic soils (Erguder et al, 2009; Kondrat‧eva et al, 2012; Lehtovirta et al, 2009; Nicol et al, 2008). Thus, the increase in archaeal band number in the planted treatments as the pH declined (Table 1) may correspond to increases in some of these acidophilic archaeal populations (Kondrat’eva et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…iron oxidizers) and Crenarchaeota ( e.g . sulfur oxidizers) are actually favored in acidic soils (Erguder et al, 2009; Kondrat‧eva et al, 2012; Lehtovirta et al, 2009; Nicol et al, 2008). Thus, the increase in archaeal band number in the planted treatments as the pH declined (Table 1) may correspond to increases in some of these acidophilic archaeal populations (Kondrat’eva et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The leaders in leaching of metals were the acidophilic chemolithotrophic bacteria (ACB), including the genera Acidithiobacillus, Sulfobacillus, Leptospirillum, Acidimicrobium, Acidianus, Ferroplasma [12,14,20,24,28,38], and for that reason this groups of bacteria were studied. The taxonomy of bacteria of Acidithiobacillus is based on their relationship to energy supply, mineral background of the culture medium with adding fer rous iron compounds in the form FeSO 4 ×7H 2 O (44.5 g/dm 3 ), elementary sulfur (5.0 g/dm 3 ) and sodium thiosulfate Na 2 S 2 O 3 (5.0 g/dm 3 ) [20,28].…”
Section: Methodsmentioning
confidence: 99%
“…Evaluation of the biogeochemical activity has showed that under natu ral conditions these microorganisms played important role in leaching of metals from sulphide ores. Similar processes have occurred in the technogenic wastes which de rived from the corresponding natural substrates [16,24,29,41]. The processing of pri mary mineral raw materials in the hostile environment and further accumulation and preservation of generated waste and heaps with changing of temperature, acidity, con tent of high concentrations of heavy metals have made conditions for a wide variety of their own microbiota [16,17,34].…”
Section: Introductionmentioning
confidence: 99%
“…These are the mineralogical and elemental composition of the sub strate to be oxidized, temperature, pH value, and the presence of organic substances [3].…”
Section: Introductionmentioning
confidence: 99%